Soft Tissue Mobilization Techniques in The Rehabilitation of Soccer-Related Myofascial Tears : A Comprehensive Systematic Review - Resaka Yudha Prawira; Bagas Ryan Kusuma (The International Journal of Medical Science and Health Research, 2026)
Introduction: Myofascial tears are prevalent in soccer, often leading to significant recovery times and high reinjury rates. Soft tissue mobilization (STM) techniques, including instrument-assisted soft tissue mobilization (IASTM) and myofascial release (MFR), are widely used in rehabilitation, yet their specific efficacy for soccer players with myofascial tears remains unclear. This systematic review synthesizes evidence on the effectiveness of STM for this specific population and injury type. Methods: A systematic review was conducted, screening 80 sources that investigated STM techniques in populations including soccer players or athletes with musculoskeletal conditions. Studies were included if they reported on outcomes such as pain, range of motion (ROM), strength, function, or return-to-play. Data on study design, participant characteristics, interventions, and outcomes were extracted and synthesized. Results: The review revealed significant heterogeneity in study quality and findings. For soccer players, specific evidence supports the use of MFR and IASTM for improving hamstring flexibility (2,4,5,62) and restoring hip ROM (8). Positive effects on pain and pressure pain thresholds were also observed (1,3,7). However, the largest and most rigorous meta-analyses (9,31) found no clinically meaningful benefit of IASTM for pain or function when added to other treatments, citing very low-quality evidence. A sham-controlled trial suggested that non-specific effects may account for much of the observed benefit (10). For return-to-sport, structured, exercise-based programs (11,12) showed stronger evidence than STM alone. Discussion: The evidence for STM in soccer myofascial tears is strongest for short-term ROM improvements and as an adjunct to exercise for pain management. Positive soccer-specific findings are often from studies targeting specific deficits like hamstring tightness (2,4,5) or myofascial trigger points (7). The discrepancy between these and null meta-analyses likely stems from differences in study quality, outcome measures, and the pooling of heterogeneous populations and techniques (9). Notably, STM appears to produce effects comparable to other manual techniques, suggesting the mechanical stimulus itself is key (37,70,74). The most robust return-to-sport outcomes are achieved through comprehensive, exercise-based, multifactorial rehabilitation programs (11,13,14). Conclusion: Soft tissue mobilization techniques, including MFR and IASTM, can be effective adjuncts in the rehabilitation of soccer players with myofascial injuries, particularly for improving range of motion and managing pain. However, they should not be considered standalone treatments. Their greatest value is within a structured, exercise-centered rehabilitation program that includes progressive loading and sport-specific functional training. Future high-quality, sham-controlled trials in homogenous soccer player populations with specific myofascial tears are needed.